SOME APPROACHES ON THE OFFENSE OF MURDER OR INJURY OF THE NEWBORN COMMITTED BY THE MOTHER, PROVIDED IN ARTICLE 200 OF THE NEW CRIMINAL CODE - MIHAELA ROTARU (Challenges of the Knowledge Society)
In addition to the innovations included in the new Criminal Code, the legislator of this legal act makes a number of amendments to the existing institutions and offenses in the criminal law. Such a situation is encountered for the offense of murder or injury of the newborn committed by the mother provided in Art. 200 N.C.C., offense that partly corresponds to the offense of infanticide described in Art. 177 of the Criminal Code in force. The legislator considered it necessary to also criminalize in the new Criminal Code the act of injury of the newborn committed by the mother, along with the action of killing, a situation that rightly caused the change of the marginal name of the offense. Moreover, another interesting aspect that also constitutes the focus of our approach is represented by the two phrases which are different from those in the legal text in force, i.e. ,,immediately after birth but not later than 24 hours" and ,,state of mental disorder”, which are designed to equalize the views expressed in the criminal literature regarding the analyzed crime and the practice in the field.